Prokaryotic Community Succession in Bulk and Rhizosphere Soils Along a High-Elevation Glacier Retreat Chronosequence on the Tibetan Plateau - Liu, Jinbo; Kong, Weidong; Xia, Pinhua; Zhu, Chunmao; Li, Xiangzhen (Frontiers in Microbiology, 2021)
Early colonization and succession of soil microbial communities are essential for soil development and nutrient accumulation. Herein we focused on the changes of pioneer prokaryotic communities in rhizosphere and bulk soils along the high-elevation glacier retreat chronosequence, the northern Himalayas, Tibetan Plateau. Rhizosphere soils showed substantially higher levels in total organic carbon, total nitrogen, ammonium and nitrate than bulk soils. The dominant prokaryotes were Proteobacteria, Actinobacteria, Acidobacteria, Chloroflexi, Crenarchaeota, Bacteroidetes, and Planctomycetes, which totally accounted for more than 75% in relative abundance. The dominant genus Candidatus Nitrososphaera occurred at each stage of the microbial succession. Soil prokaryotic α-diversity: richness and evenness mild succession along chronosequence. LEfSe analysis demonstrated that Proteobacteria (especially Alphaproteobacteria) and Actinobacteria significantly enriched in rhizosphere soils, compared with bulk soils. Actinobacteria, SHA_109, and Thermoleophilia; Betaproteobacteria and OP1.MSBL6; Planctomycetia and Verrucomicrobia were separately enriched, at each of the three sample sites. Prokaryotic communities’ composition was substantially changed with bulk and rhizosphere soils, and sampling sites, indicating that the communities were dominantly driven by plants and habitat-specific effects in the deglaciated soils. Additionally, the distance to the glacier terminus also played a significant role in driving the change of prokaryotic communities in both bulk and rhizosphere soils. Soil C/N ratio exhibited a greater effect on prokaryotic communities in bulk soils than rhizosphere soils. These results indicate that plants, habitat and glacier retreat chronosequence collectively control prokaryotic community composition and succession.